Coconut husk retting effluent and fish species diversity in the river Pantikal, Kanyakumari district - Jeyaraj, C Thampi; Selvaraj, D; Jones, R D Stevens; Chitra, G (Indian Journal of Fisheries, 2011)
River pollution by industrial effluents is prevalent in India and the less industrializedKanyakumari district of Tamil Nadu is not an exception to this. Fishspecies diversity studies undertaken at two selected stations of river Pantikal,which is loaded with coconut husk retting effluent showed that the station receivingthe effluent is moderately polluted during post monsoon season andheavily polluted during summer leading to poor biodiversity and deterioration ofwater quality. Unless concrete measures are taken to abate pollution of thistype, the water quality will further deteriorate resulting in mass fish mortality